2015
DOI: 10.1074/jbc.m114.610063
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Unique Intracellular Domains to Switchlike Biosensing by Toll-like Receptor 4

Abstract: Background: TLR4 is an important receptor, promoting both protective immunity and inflammatory diseases. Results: A revised model of TLR4 signaling is proposed, based upon new observations. Conclusion: TLR4 forms an autoinhibitory complex in the absence of ligand; disrupting this complex induces downstream signaling.Significance: This new mechanism may explain TLR4 responsiveness to diverse ligands and guide the design of novel therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…It appears that only the disulfide HMGB1 binds to MD-2, an interaction that is of critical importance for HMGB1-mediated cytokine/chemokine production and the development of subsequent tissue injury [34]. On the other hand, ROS/TLR4-coupled activation could be due to a reversible “atomic” specificity in which specific sulfur atoms on cysteine residues [36, 37] uniquely expressed in the intracellular domains of TLR4 [38] may play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that only the disulfide HMGB1 binds to MD-2, an interaction that is of critical importance for HMGB1-mediated cytokine/chemokine production and the development of subsequent tissue injury [34]. On the other hand, ROS/TLR4-coupled activation could be due to a reversible “atomic” specificity in which specific sulfur atoms on cysteine residues [36, 37] uniquely expressed in the intracellular domains of TLR4 [38] may play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…LPS binding to MD2 promotes a conformational change that induces TLR4 ectodomain dimerization, leading to dissociation of TIC from TLR4. In the absence of TIC, the TIR domain of TLR4 spontaneously dimerizes and induces adapter recruitment and downstream signaling (16). It has been shown that homoassociation of TLR4 occurs prior to its translocation and clustering to lipid rafts (17).…”
mentioning
confidence: 99%
“…В отсутствие TIC домены TLR4 TIR спонтанно димеризуются и запускают дальнейший сложный каскад реакций в клетке (цит. по [10])…”
Section: рисунок 2 предполагаемая модель передачи сигнала через Tlr4unclassified